2016
DOI: 10.1093/mnras/stw1898
|View full text |Cite
|
Sign up to set email alerts
|

XMM–Newtonstudies of the supernova remnant G350.0−2.0

Abstract: We report the results of XMM-Newton observations of the Galactic mixed-morphology supernova remnant G350.0−2.0. Diffuse thermal X-ray emission fills the north-western part of the remnant surrounded by radio shell-like structures. We did not detect any X-ray counterpart of the latter structures, but found several bright blobs within the diffuse emission. The X-ray spectrum of the most part of the remnant can be described by a collisionally-ionized plasma model vapec with solar abundances and a temperature of ≈ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This is a crude approximation because actual Fe-L lines are ensembles of many different transitions, but it turned out to be sufficient for the present data given the energy resolution and statistics. Similar treatments are found in the analysis of other SNRs (e.g., Sawada & Koyama 2012, Sato et al 2016, and Karpova et al 2016. We found that combinations of a low-temperature CIE with the solar abundance and a high-temperature NEI with variable abundance gave relatively good fits.…”
Section: Single Ejecta Modelssupporting
confidence: 88%
“…This is a crude approximation because actual Fe-L lines are ensembles of many different transitions, but it turned out to be sufficient for the present data given the energy resolution and statistics. Similar treatments are found in the analysis of other SNRs (e.g., Sawada & Koyama 2012, Sato et al 2016, and Karpova et al 2016. We found that combinations of a low-temperature CIE with the solar abundance and a high-temperature NEI with variable abundance gave relatively good fits.…”
Section: Single Ejecta Modelssupporting
confidence: 88%
“…Williams et al (2020). Some "blobs" with a significant 1.25 keV line emission were found also in a mixed-morphology SNR G350.0-2.0 by Karpova et al (2016). Therefore, more observations are needed to confirm or reject the apparent spectral excess in SNR G18.95-1.1.…”
Section: Discussionmentioning
confidence: 99%
“…The ROSAT map of this source (see Fig. 1 in Karpova et al 2016) covers the entire SNR, showcasing that 350.0-2.0 is indeed a mixed morphology SNR. Leahy & Tian 2005;Araya 2013;Arias et al 2019b;Xiao et al 2022).…”
Section: Introductionmentioning
confidence: 85%
“…The authors identify some elongated filaments that could be associated with the SNR, and favour an interpretation whereby the source is actually more than one SNR aligned along the line of sight. Karpova et al (2016) observed G 350.0-2.0 with XMM-Newton, finding a plasma with mostly solar abundances and some regions of overabundant Fe. They estimated a distance of approximately 3 kpc, corresponding to a SNR diameter of 20 pc, and an age of ∼10 4 yr.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation